A DNA-damaging sesquiterpene and other constituents from Frullania nisquallensis - Kim, Y. C.; Bolzani, Vanderlan da Silva [UNESP]; Baj, N.; Gunatilaka, AAL; Kingston, DGI (Georg Thieme Verlag, 1996)
Bioassay-guided fractionation of an MeCOEt extract of Frullania nisquallensis Sull. has furnished a DNA-damaging sesquiterpene, costunolide (1), and two inactive compounds, a sesquiterpene (-)-frullanolide (2) and a tridepside tenuiorin (3). C-13-NMR data of 3 are reported.